2019
DOI: 10.1021/acsabm.9b00502
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Resistant, Transparent, Free-Standing Films Prepared from Complex Coacervates

Abstract: We report the fabrication, properties, and bacteria-resistance of polyelectrolyte complex (PEC) coatings and free-standing films. Poly(4-styrenesulfonic acid), poly(diallyldimethyl-ammonium chloride), and salt were spin-coated into PEC films. After thermal annealing in a humid environment, highly transparent, mechanically strong, and chemically robust films were formed. Notably, we demonstrate that PEC coatings significantly reduce the attachment of Escherichia coli K12 without killing the micro-organisms. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 71 publications
2
37
0
Order By: Relevance
“…In particular, a seminal report by Wang and Schlenoff demonstrated that solid precipitates and liquid coacervates could exist along a continuum of salt concentration ( Figure 10). 50 This idea of salt-driven plasticization, or 'salo- plasticity' has opened up a tremendous range of opportunities for using salt to process polyelectrolyte complex materials as liquid coacervates, and then solidify the materials by the removal of salt, and a range of accounts describing ultracentrifuged [190][191][192][193] or extruded materials, 194 spin-coated films, 195,196 3D printed structures, 197 and electrospun fibers 65,198,199 have been reported.…”
Section: Coacervate Rheology and The Complex/coacervate Continuummentioning
confidence: 99%
“…In particular, a seminal report by Wang and Schlenoff demonstrated that solid precipitates and liquid coacervates could exist along a continuum of salt concentration ( Figure 10). 50 This idea of salt-driven plasticization, or 'salo- plasticity' has opened up a tremendous range of opportunities for using salt to process polyelectrolyte complex materials as liquid coacervates, and then solidify the materials by the removal of salt, and a range of accounts describing ultracentrifuged [190][191][192][193] or extruded materials, 194 spin-coated films, 195,196 3D printed structures, 197 and electrospun fibers 65,198,199 have been reported.…”
Section: Coacervate Rheology and The Complex/coacervate Continuummentioning
confidence: 99%
“… 31 35 Porous saloplastic materials are obtained by centrifugation 31 , 36 and electrospinning 37 of coacervate phases or by desalting a homogeneous PE solution in between semipermeable membranes. 38 In addition, doped PECs can be extruded to obtain dense materials in various shapes (tape, tube, rod, and fiber) 32 , 33 or spin-coated, 34 , 39 cast, 40 , 41 or pressed in between templates 42 , 43 to obtain transparent films. Moreover, some of the saloplastics show self-healing behavior which can operate under room temperature and tuned by type of salt.…”
Section: Introductionmentioning
confidence: 99%
“… 211 Using salt as a plasticizer allowed the PECs to be formed in different shapes and sizes, proving that PECs are actually processable just like thermoplastics. 33 , 212 214 This accelerated the research on saloplastic materials, and many papers have been published on advanced functional saloplastics with self-healing, 215 217 shape recovery, 218 patternability, 219 antifouling, 18 gas barrier, 220 and chemical stability 212 features. Additionally, incorporation of PECs with other kinds of materials, such as nanoparticles, is also demonstrated indicating it is possible to have materials with even more advanced functions.…”
Section: Polyelectrolytes and Polyelectrolyte Complexes As Free-standing Membranesmentioning
confidence: 99%
“…The literature on this is predominantly on copolymer membranes which are prepared with NIPS. There are a few studies on antifouling saloplastic material, 18 and to our knowledge, the work of Willott et al. is the only study that investigates stimuli-responsive and self-cleaning functions of homopolymer free-standing membranes 251 prepared with APS.…”
Section: Polyelectrolytes and Polyelectrolyte Complexes As Free-standing Membranesmentioning
confidence: 99%
See 1 more Smart Citation